Security Implications of Biometric Gesture Recognition - Patle, Bharti; Banothe, Roshni; Kumbhare, Bhagyashree; Laxane, Yamini (Indian Journal of Computer Science, 2025)
In this research, the emerging field of biometric gesture recognition is explored as a novel approach to user authentication within Human-Computer Interaction (HCI). By utilizing distinctive physical movements such as hand gestures, finger patterns, or full-body motions, this technology offers a touchless and user-friendly alternative to conventional input methods. While the usability and accessibility of gesture-based systems are noteworthy, it was observed that they also introduce significant security challenges. Through this study, key security implications including the risks of spoofing attacks, data interception, replay attacks, and potential breaches of user privacy are investigated. The robustness of existing gesture recognition algorithms is analyzed and common threat models are evaluated to understand where current security frameworks may fall short. Additionally, the authors examine the balance between user convenience and system security, and strategies are proposed to enhance the resilience of these systems, such as implementing multimodal authentication, live detection, and encrypted gesture templates. This work aims to contribute to the development of more secure and reliable gesture-based biometric systems for future applications.